Multi-gene phylogeny reveals a new genus and species of Hapalidiales (Rhodophyta) from Antarctica: Thalassolithon adeliense gen. & sp. nov. Issue 1 (2nd January 2023) - Trentin, Riccardo; Moschin, Emanuela; Grapputo, Alessandro; Rindi, Fabio; Schiaparelli, Stefano; Moro, Isabella
ABSTRACT: Non-geniculate coralline algal specimens were collected in 2013 during the XXVIII Italian Expedition to Antarctica in Adélie Cove (Terra Nova Bay; Ross Sea) and deposited in the collections of the Italian National Antarctic Museum (MNAIT, Section of Genoa). Specimens were characterized through a polyphasic approach combining DNA sequence data obtained for four genes ( psb A, rbc L, 18S rDNA and cox 1) with morpho-anatomical observations. DNA sequences revealed that all specimens belonged to the same species. Phylogenetic reconstructions unambiguously recovered this alga as a member of the order Hapalidiales, but without any close relationship to a genus of this order currently recognized on a molecular phylogenetic basis. Instead, it formed a well-supported lineage with specimens named 'Hapalidiales sp. ZH-Twist-2019', collected in New Zealand, for which no formal assignment at genus level has been proposed. Species delimitation methods (ABGD, PTP, GMYC) applied to the psb A dataset indicated that the Adélie Cove coralline alga is a distinct species from all other known hapalidialean species for which such sequences are available. A new genus, Thalassolithon gen. nov ., is proposed for T. adeliense sp. nov.